Pencabutan dan Pembatasan Hak Memilih dari Ekspatriat: Sebuah Kajian Perspektif Konstitusional - Rusdiana, Shelvi; Hutauruk, Rufinus Hotmaulana; Situmeang, Ampuan (Legal Spirit, 2024)
The right to vote as a fundamental human right in a democratic country like Indonesia, in fact cannot always be guaranteed to be implemented and its benefits can be realized. The problem of election integrity in Indonesia, which has not improved, has encouraged Indonesia to continue to update its democratic party implementation system, including considering various existing alternatives. Revoking and limiting expatriates' right to vote is a practice that has actually been carried out by other countries, to improve the integrity of elections. This research aims to analyze the possibility of revoking and/or limiting the right to vote from expatriates as an effort to increase election integrity, with a constitutional lens. This analysis is supported by normative legal research methods, with a statutory approach and a comparative approach. The research results found that although revoking the right to vote from expatriates is an unconstitutional option and has not been implemented, the government can implement limiting the right to vote from expatriates to cover the normative gap that exists regarding citizenship, while increasing the accuracy of election list data, by implementing several policies that have been implemented by other countries